Eelgrass communities in southeast Alaska (eelgrass density and biomass, epiphytes, and epifauna) - Wendel Raymond; Tiffany Stephens; Ginny Eckert; Lia Domke (Knowledge Network for Biocomplexity, 2018)
Intertidal seagrass community data were collected during summertime 2017 - 2019 (May-August) on western Prince of Wales Island, Alaska. In 2017, the purpose of these data was to characterize the eelgrass community so that analysis of trophic interactions could be assessed along a gradient of sea otter occupation for an NSF-funded project: Apex Predators, Ecosystems, and Community Sustainability (APECS, http://apecs-ak.org/). In 2018 and 2019, methods were slightly different and the purpose was to evaluate eelgrass community at a subset of sites and look at potential interannual changes. In 2017, data were collected at 21 independent sites. At each site, the coordinates, sampling date + times, and tidal elevation were recorded. At each site, one 100 m transect was laid horizontally along a shoreline, along which data were collected in 8 quadrats. Data types include eelgrass shoot count and biomass per replicate shoots, flowering eelgrass shoot count, rhizome biomass paired with shoots, rhizome internode lengths, two-dimensional percent cover of epiphytes and macroalgae within a quadrat, biomass of epiphytes wiped from eelgrass shoots, and counts and biomass of epifauna collected from eelgrass shoots. In 2018 and 2019, the same data were collect except for rhizome biomass/internode length. Other datasets to support this work are also archived with KNB and are searchable using the identifier “APECS_alaska”.